The impact of e-learning on the cognitive level in the Corona crisis (Al-Academy, 2021)
E-learning is a necessity imposed by the Corona pandemic, which has disrupted various educational institutions in the world, but some of these institutions have not been affected and education has continued with them, due to their flexible educational system that was able to employ technology in the continuity of the educational process in the so-called e-learning, because It has characteristics that make it the most suitable alternative to avoid the consequences of the Corona pandemic and its damage to the educational process, as e-learning is one of the modern methods that contribute to enhancing the effectiveness of the learner, and enabling him to assume greater responsibility compared to traditional education, so the learner becomes more able to discover And analysis, installation and acquisition of high-level learning skills based on the foregoing, the researcher addresses the concept of e-learning, its types, advantages and disadvantages, and how it can be used as an educational system in light of the Corona pandemic?The current research aims to identify:1- The impact of e-learning on the cognitive level in light of the Corona crisis.2- To verify the aim of the research, the following hypotheses were developed:3- There are no statistically significant differences between the average scores of the experimental group students and the average scores of the control group students in the acquisition of technological concepts test.4- There are no statistically significant differences between the average scores of the experimental group with low and high achievement and the average scores of their peers from the control group in the technological concepts acquisition test